Extending the limits of direct force measurements: colloidal probes from sub-micron particles. Issue 27 (29th June 2017) - Helfricht, Nicolas; Mark, Andreas; Dorwling-Carter, Livie; Zambelli, Tomaso; Papastavrou, Georg
Abstract : Long-range interactions between sub-micron silica particles have been determined by means of a combination of atomic force microscopy (AFM) with nanofluidics, which allows for a temporary immobilization of small probe particles by an external pressure. Abstract : Direct force measurements by atomic force microscopy (AFM) in combination with the colloidal probe technique are widely used to determine interaction forces in colloidal systems. However, a number of limitations are still preventing a more universal applicability of this technique. Currently, one of the most significant limitations is that only particles with diameters of several micrometers can be used as probe particles. Here, we present a novel approach, based on the combination of nanofluidics and AFM (also referred to as FluidFM-technique), that allows to overcome this size limit and extend the size of suitable probe particles below diameters of 500 nanometers. Moreover, by aspiration of colloidal particles with a hollow AFM-cantilever, the immobilization process is independent of the particle's surface chemistry. Furthermore, the probe particles can be exchanged in situ . The applicability of the FluidFM-technique is demonstrated with silica particles, which are also the types of particles most often used for the preparation of colloidal probes. By comparing 'classical' colloidal probes, i.e. probes from particles irreversibly attached with glue, and various particle sizes aspirated by the FluidFM-technique, we can quantitatively evaluate the instrumental limits. Evaluation of the force profiles demonstrate that even for 500 nm silica particles the diffuse layer properties can be evaluated quantitatively. Therefore, direct force measurements on the level of particle sizes used in industrial formulations will become available in the future.